2016
DOI: 10.21608/asejaiqjsae.2016.2238
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Efficacy on Resistance of Garlic Plants (Allium sativum, L.) to Water Salinity Stress on Growth, Yield and its Quality

Abstract: This experiment was conducted and replicated during both winter seasons of 2013/2014 and 2014/2015, respectively at Soil Salinity Laboratory, Alexandria. This research was conducted to study the effects of water salinity and the application of salicylic acid (SA) on garlic growth performance, yield and its quality. Four levels of saline irrigation water treatments were used; i.e., 435 (fresh tap water as a control), 1500, 3000 and 4500 ppm. Three levels of salicylic acid treatments were foliar applied on garli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…SA improves mineral uptake from the roots toward other parts of the plant. Shama et al. (2016) demonstrated that an exogenous spray of SA 300 ppm revealed excellent vegetative and reproductive growth with enhanced level of minerals, such as potassium, while a decrease in sodium levels was recorded in garlic growing under salinity.…”
Section: Salicylic Acid Improves Salt Tolerance By Scavenging Toxic R...mentioning
confidence: 97%
“…SA improves mineral uptake from the roots toward other parts of the plant. Shama et al. (2016) demonstrated that an exogenous spray of SA 300 ppm revealed excellent vegetative and reproductive growth with enhanced level of minerals, such as potassium, while a decrease in sodium levels was recorded in garlic growing under salinity.…”
Section: Salicylic Acid Improves Salt Tolerance By Scavenging Toxic R...mentioning
confidence: 97%